2012
DOI: 10.1016/j.yebeh.2012.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with life domains in people with epilepsy

Abstract: While commonly used quality-of-life instruments assess perceived epilepsy-associated limitations in life domains and formally document patient concerns, less is known of community-dwelling adults with epilepsy about their satisfaction with broader life domains, such as satisfaction with housing, education, neighborhood, ability to help others, and achievement of goals. The purpose of this study was to examine satisfaction with life domains in a representative sample of community-dwelling adults with self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 36 publications
2
12
0
1
Order By: Relevance
“…With regard to other comparative studies, our findings, likewise, suggested the importance of both objective [21,22] and subjective variables [23][24][25], yet our findings only partially supported the role of objective variables since employment and leisure activities were not significant predictors of life satisfaction among the study sample.…”
Section: Discussionsupporting
confidence: 56%
“…With regard to other comparative studies, our findings, likewise, suggested the importance of both objective [21,22] and subjective variables [23][24][25], yet our findings only partially supported the role of objective variables since employment and leisure activities were not significant predictors of life satisfaction among the study sample.…”
Section: Discussionsupporting
confidence: 56%
“…People with epilepsy (PWE) not only suffer from uncontrolled seizures and face treatment complexity but are also at a higher risk for comorbidities [2] (e.g., heart disease, emphysema, or cancer), impaired mental health [3] (e.g., serious psychological disorder or insomnia), and worse health-related quality of life [4,5]. Improving appropriate medical care for PWE is a national objective for the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…PWE report feeling isolated and dependent on others, experience interpersonal and social difficulties, and perceive stigmatization due to their condition [7, 10, 11]. Additionally, PWE consistently report lower quality of life, higher levels of depressive symptoms, and greater impairment of physical and social functioning compared to people without epilepsy [1214]. Perceptions of living with epilepsy range from acceptance and living a normal life to feeling a loss of control and giving up hope of recovery [15].…”
Section: Introductionmentioning
confidence: 99%